2010
DOI: 10.1097/jcp.0b013e3181f28dff
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-Blind Comparison of Risperidone Versus Low-Dose Risperidone Plus Low-Dose Haloperidol in Treating Schizophrenia

Abstract: Monotherapy is recommended for schizophrenia treatment, but the risk-benefit issue of antipsychotic drug combination (except for clozapine) remains unclear. Risperidone, an atypical antipsychotic drug, has a lower incidence of extrapyramidal syndrome but higher risks of prolactinemia and metabolic syndrome than haloperidol, a typical agent. This study compared efficacy and safety of risperidone monotherapy versus low-dose risperidone plus low-dose haloperidol in schizophrenia. In this 6-week, double-blind stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Other authors found similar results, by using data from Medicaid claims 20, 21 , pharmacy claims 15, 22, 23 , studying outpatients with non-affective psychosis 24 , studying patients admitted in a state hospital 25, 26 and studying patients in East Asia 27 and Europe 28–32 . By contrast, in a double-blind study 33 , the combination of low dose haloperidol and low dose risperidone was associated with lower scores in the Simpson-Angus Scale compared to risperidone alone in full doses. However, this APP regimen specifically attempted to avoid increased net dopamine blockage.…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…Other authors found similar results, by using data from Medicaid claims 20, 21 , pharmacy claims 15, 22, 23 , studying outpatients with non-affective psychosis 24 , studying patients admitted in a state hospital 25, 26 and studying patients in East Asia 27 and Europe 28–32 . By contrast, in a double-blind study 33 , the combination of low dose haloperidol and low dose risperidone was associated with lower scores in the Simpson-Angus Scale compared to risperidone alone in full doses. However, this APP regimen specifically attempted to avoid increased net dopamine blockage.…”
Section: Resultsmentioning
confidence: 68%
“…Another approach that was found to be helpful in reducing prolactin levels was the combination of antipsychotics in low doses. Lin 33 , in a 6-week, double-blind study, found that patients taking low dose risperidone plus low dose haloperidol had lower prolactin levels compared to patients taking full dose risperidone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…28 A review by Gö ren et al 30 observed that 'limited data' support the use of antipsychotic polypharmacy for patients with treatmentresistant illness. However, in a double-blind randomised study 31 a small group of patients with schizophrenia were randomised to receive either risperidone monotherapy or a combination of low-dose risperidone and low-dose haloperidol. Although no significant difference was observed between the two groups in symptom response, the result favoured the polypharmacy group in terms of the side-effect profile.…”
Section: 10mentioning
confidence: 99%
“…For example, in a recent study, Lin et al (2010) compared two groups: one receiving both risperidone (2 mg/d) and haloperidol (2 mg) and other on monotherapy (risperidone 4 mg/d). While the two treatments were similar in efficacy, the monotherapy group had higher prolactin levels and extrapyramidal side effects.…”
Section: Discussionmentioning
confidence: 98%